Advances in Robotic-Assisted Radical Prostatectomy over Time. (12th November 2013) - Jacobs, Emma F. P.; Boris, Ronald; Masterson, Timothy A.
Abstract : Since the introduction of robot-assisted radical prostatectomy (RALP), robotics has become increasingly more commonplace in the armamentarium of the urologic surgeon. Robotic utilization has exploded across surgical disciplines well beyond the fields of urology and prostate surgery. The literature detailing technical steps, comparison of large surgical series, and even robotically focused randomized control trials are available for review. RALP, the first robot-assisted surgical procedure to achieve widespread use, has recently become the primary approach for the surgical management of localized prostate cancer. As a result, surgeons are constantly trying to refine and improve upon current technical aspects of the operation. Recent areas of published modifications include bladder neck anastomosis and reconstruction, bladder drainage, nerve sparing approaches and techniques, and perioperative and postoperative management including penile rehabilitation. In this review, we summarize recent advances in perioperative management and surgical technique for RALP.